Taking comedy seriously stand-up's dissident potential in mass culture - Donian, Jennalee (Politics and comedy: critical encounters, 2019)
"This book contextualizes contemporary stand-up comedy within the wider socio-political terrain of neoliberal capitalism, contributing to a more complex and developed understanding of the relation of jokes and humor to the unconscious mind in its relation to ideology and discourse"--